Examining intraindividual variability of urinary gluten immunogenic peptides compared to the lactulose-mannitol ratio in healthy volunteers: implications for clinical assessment of intestinal permeability - Rodríguez-Ramírez, Raquel; Fernández Peralbo, María Auxiliadora; Cebolla, Ángel; Sousa, Carolina (Frontiers in Immunology, 2025)
IntroductionThe intestinal barrier plays a crucial role in preventing the translocation of harmful substances. Intestinal permeability is commonly assessed using the lactulose-mannitol ratio (LMR) test, which measures absorption of non-metabolizable sugars. However, it does not reflect permeability to larger, potentially antigenic molecules such as proteins. Urinary gluten immunogenic peptides (u-GIP), derived from gluten, have emerged as promising biomarkers, showing sensitivity to mucosal disruption. This study compared the intraindividual variability of u-GIP and LMR under fasting conditions in healthy volunteers to assess the consistency and reproducibility of both methods for evaluating intestinal barrier function.MethodsTwelve healthy adult volunteers underwent a controlled dietary protocol and repeated intestinal permeability testing on three separate days. After a fasting period, each participant ingested gluten, lactulose and mannitol. Urine samples were collected at 0–6 and 0–15-hour intervals. GIP levels were assessed using a lateral flow immunoassay, while lactulose and mannitol were quantified via ion chromatography. Intraindividual variability was evaluated using coefficients of variation (CV) and intraclass correlation coefficients (ICC) and the results were compared with reference ranges.ResultsExcretion patterns for u-GIP, lactulose and mannitol were generally similar, with detection within the first 3 hours and peaks around 4–5 hours. u-GIP consistently exhibited lower intraindividual variability than the traditional LMR. The CV for u-GIP excretion remained within an acceptable range (~20%) and its ICC reached 0.750 in the 0–15-hour interval, indicating excellent reproducibility. In contrast, the LMR showed higher CVs and poor ICC values, which only improved modestly after outlier exclusion. GIP measurements consistently fell within established reference ranges across test repetitions, further supporting their stability.Discussionu-GIP demonstrated lower intraindividual variability and higher consistency than LMR, indicating its potential as a robust and reliable marker for assessing intestinal permeability. Unlike LMR, GIP showed better reproducibility across days and minimal influence from dietary fluctuations. Its advantages include direct clinical relevance as an immunogenic dietary protein marker, reduced physiological variability and non-invasive methods. These features highlight u-GIP promising potential for future clinical and research applications. However, further studies are needed to validate its effectiveness specifically in patients with altered intestinal permeability.